2022
DOI: 10.3390/cmd3010003
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and Carbonation of Alternative Binders

Abstract: The cement industry gains increasing public attention because of the high CO2 emissions for which it is accountable. One approach to improve the carbon footprint of cement production is the development of alternative binders, which can be produced with less energy consumption. These alternative binders have a reduced clinker to cement ratio or contain no Portland cement at all. For the corrosion protection of the reinforcement, the same requirements apply as for standardized types of cement. To perform this ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 78 publications
1
6
0
2
Order By: Relevance
“…Comparable to Ref I, the proportion of the X-ray amorphous phase after 28 d is 41 %. The SEM images and mappings described in [11] showed not completely dissolved slag particles. The X-ray amorphous content consisted of C-(A)-S-H phases.…”
Section: Ref I Andmentioning
confidence: 87%
See 3 more Smart Citations
“…Comparable to Ref I, the proportion of the X-ray amorphous phase after 28 d is 41 %. The SEM images and mappings described in [11] showed not completely dissolved slag particles. The X-ray amorphous content consisted of C-(A)-S-H phases.…”
Section: Ref I Andmentioning
confidence: 87%
“…Other phases were omitted for clarity. Furthermore, in Kraft et al [11] SEM images of the samples described here can be found. [11], the X-ray amorphous phases are mainly C-(A)-S-H phases and residues of the slag, as expected.…”
Section: Hydrationmentioning
confidence: 90%
See 2 more Smart Citations
“…Die Ergebnisse der LT-DSC in Abbildung 6 zeigen, dass die partielle Substitution des Zements durch calcinierten Ton (Referenz B) zu einer deutlichen Verringerung der Kapillarporosität führt. Die Ergebnisse der Kapillarporosität stehen in Übereinstimmung mit Werten aus der Literatur, nachdem die Verwendung von calcinierten Tonen im Beton zu einer Gefügeverdichtung beiträgt [11,12]. Dies wird auf zwei Effekte zurückgeführt.…”
Section: Abbildung 6 Masse Des Bei -20 °C Gefrierbaren Wassers Im Por...unclassified